Fabrication and characterization of nickel thin film as resistance temperature detector - Cui, Jinting; Liu, Hao; Li, Xingliang; Jiang, Shuwen; Zhang, Bin; Song, Ying; Zhang, Wanli (Vacuum, 2020)
In practical applications, thin film resistance temperature detectors (RTD) are often used in the environments that the attached substrates cannot stand high temperature. Therefore, it is necessary to prepare thin film RTDs by a low temperature process. In this study, the fabrication of nickel (Ni) thin film RTDs at low temperatures is investigated by direct-current (DC) magnetron sputtering. It is found that the dense and uniform Ni thin film can be prepared even at room temperature. The effects of sputter pressure and power on thin film microscopic morphology and structure are also investigated. The Ni thin film RTDs prepared at room temperature exhibit a value of temperature coefficient of resistance (TCR) about 3000 ppm/°C and excellent repeatability under cycling temperatures. •A method for preparing a Ni thin film having a high TCR (~3000 ppm/°C), good linearity, and reproducibility at room temperature was found•This can solve the film temperature measurement of a device that is difficult to withstand high temperatures.•It has certain effect and significance for solving some problems in the industry.